2019
DOI: 10.3390/nano9091186
|View full text |Cite
|
Sign up to set email alerts
|

Robust Polymer Nanocomposite Membranes Incorporating Discrete TiO2 Nanotubes for Water Treatment

Abstract: Polyethersulfone (PES) is a polymeric permeable material used in ultrafiltration (UF) membranes due to its high thermomechanical and chemical stability. The hydrophobic nature of PES membranes renders them prone to fouling and restricts the practical applications of PES in the fabrication of water treatment membranes. The present study demonstrates a non-solvent-induced phase separation (NIPS) approach to modifying PES membranes with different concentrations of discrete TiO2 nanotubes (TNTs). Zeta potential an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Full survey XPS spectra of RTV-SR and RTV-SR/FLG clearly showed the presence of carbon (C1s), oxygen (O1s), and silicone (Si2s and Si2p), while peaks of iron (Fe2p) [ 54 ] and titanium (Ti2s and Ti2p) [ 55 ] were observed after incorporating Fe3O4 and TiO2 in RTV-SR/FLG composites ( Figure 6 and Figure 7 ). Furthermore, in the high-resolution XPS spectra of RTV-SR, two main peaks of silicone rubber chains were observed at 102.4 eV (Si-C/O-Si-O ascribed to organic silicone) and 103.5 eV (Si-(O)x, x = 3, 4; inorganic silicone), which represented silicone backbones and side groups, respectively [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Full survey XPS spectra of RTV-SR and RTV-SR/FLG clearly showed the presence of carbon (C1s), oxygen (O1s), and silicone (Si2s and Si2p), while peaks of iron (Fe2p) [ 54 ] and titanium (Ti2s and Ti2p) [ 55 ] were observed after incorporating Fe3O4 and TiO2 in RTV-SR/FLG composites ( Figure 6 and Figure 7 ). Furthermore, in the high-resolution XPS spectra of RTV-SR, two main peaks of silicone rubber chains were observed at 102.4 eV (Si-C/O-Si-O ascribed to organic silicone) and 103.5 eV (Si-(O)x, x = 3, 4; inorganic silicone), which represented silicone backbones and side groups, respectively [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the FT‐IR spectrum of the ODPA‐treated IGZO, manifest peaks at 545, 970, 1135, 2848, and 2915 cm −1 , corresponding to OPO vibration, symmetric PO, asymmetric PO, symmetric CH 2 , and asymmetric vibration, respectively, which indicated the ODPA bonding to the oxide surface. [ 21 ] The topology of the ODPA‐treated surface of the IGZO layer was probed with noncontact mode AFM. Through a comparison with 5 × 5 µm surface topology of depending on the existence of the ODPA (Figure 2d,e), the ODPA molecules with 4–6 nm length were distributed on the surface, indicating that the ODPA molecules were evenly deposited on the IGZO surface.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that all membranes had a typical asymmetrical structure, which was composed of a dense skin layer, a fingerlike structure below, and a macrovoid structure at the bottom. Macrovoids in rPS 16 were less visible than in rPS 16 0.1 membrane [30]. Addition of nanotubes to the unmodified rPS membrane decreased the thickness of the membrane.…”
Section: Modified Membranes Characteristicmentioning
confidence: 91%